High-risk human papillomavirus infection in the prediction of poor treatment response and disease recurrence in patients with vulvovaginal condyloma. Issue 1 (January 2016) - Koo, Yu-Jin; Kim, Yeon-Sun; Min, Kyung-Jin; Hong, Jin-Hwa; Lee, Jae-Kwan
Abstract: Objective: To determine the predictive factors for progression and recurrence of vulvovaginal condyloma (VVC), with a specific focus on high-risk HPV (HR-HPV) infections. Methods: Retrospective data were collected from 48 patients who were diagnosed with VVC and treated with topical trichloroacetic acid application or laser therapy during 2003–2014 at a hospital in South Korea. The diagnoses were made based on the presence of exophytic condylomatous lesions as assessed by direct visual inspection regardless of whether a biopsy was performed. Results: Overall, 18 patients (50.0% of those with a test result) were positive for HR-HPV. Three-quarters of the patients with a poor treatment response had abnormal cytologies, and abnormal cytology was a risk factor for a poor response (odds ratio, 4.33 [95% confidence interval, 1.05–17.84]). During a median follow-up of 24 months, VVC recurred in seven (14.6%) patients. A high viral load (more than 50 relative light units) of HR-HPV was significantly associated with recurrence (odds ratio, 7.42, 95% confidence interval, 1.19–46.18). Conclusion: A high HR-HPV load is a risk factor for recurrence, but is not related to treatment response. A poor treatment response is more related to abnormal cytology than it is to viral load.